PEKERJAAN PEMELIHARAAN PERIODIK PADA RUAS JALAN TOL PALIMANAN-KANCI DENGAN JAMINAN PERFORMA ZERO POTHOLE TAHUN 2014 PT. JASA MARGA (PERSERO) TBK. CABANG PALIKANCI - , M. ZUHDI FADHLI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Highway (in Indonesia also called as a free way) is a alternative road to solved a traffic jam or for the cut the distance to other place. A highway is a part of national road system and for using highway, a user must be paid based on cost. PT. Jasa Marga (Persero) Tbk. to maintenance Palimanan-Kanci Highway, such maintenance periodic project. This maintenance project to give back highway perform form a bad perform to excellent perform to be upgrading quality service for the suit operational standard. Maintenance process periodic to be upgrading highway structure such as, Scrapping, Filling and Overlay (SFO). Scrapping operation to be get peeled off slick flexible pavement existing., Scrapping Operation to use Cold Milling, and Dump Truck. Filling Operation to be fill slick flexible pavement and Overlay Operation to be fill slick surface corse flexible pavement. Filling and Overlay operation to use Asphalt Finisher, Dump Truck, Tandem Roller, and Pneumatic Tyred Roller. Based on observation could concluded, there are several noticed wich on implementation. There were need coordination between related person about project, extra controlling project, more applying SMK3 rules and controlling routine to smoothnes project and minimalized overdue project.